Didier Rey, Le timbre-poste, une mémoire de l’histoire européenne 1840-2020 (Rennes : Presses Universitaires de Rennes, 2025), 431 pages - MÂRZA, Radu (Studia Universitatis Babeș-Bolyai Historia, 2025)
In our times, philately, and the more general habit of collecting objects such as stamps, banknotes and coins, postcards and other collectibles, is in decline. Perhaps that is why historians are increasingly turning their attention to these fascinating fields of research. Not only is (or was) philately the most widespread hobby, but the historical research dedicated to it is also surprisingly extensive. There are entire libraries dedicated to this subject around the world, a fact confirmed by the book published in early 2025 by Didier Rey, historian, professor at the University of Corsica and, last but not least, avid stamp collector. In Romania, the historical analysis of philately is in its infancy, but historical research is not lacking (see, for example, the book by Cristian Andrei Scăiceanu, Istoria mișcării filatelice din România [A history of the Philatelic Movement in Romania] (București: Ed. Oscar Print, 2011). Didier Rey’s book is dedicated to European philately between 1840-2020. However, the geographic framework extends well beyond Europe, because the author (also) takes into account the huge and complex system of colonies, possessions and territories held by European countries outside the Old Continent. Nonetheless, we should note that the author starts from the premise – to which we fully subscribe – that the stamp is a keeper of European historical memory, regardless of whether it is colonial history or the history of European countries themselves. The book demonstrates a thorough knowledge of European political history (including its overseas dimensions), but also of modern and contemporary world history. At the same time, the author is well acquainted with the ideologies circulating in Europe during this period of almost two centuries and understands philately as an instrument for affirming, expressing and manifesting ideologies – for example, national ideologies, not coincidentally citing the fundamental book of French historian Anne-Marie Thiesse, La création des identités nationales. Europe XVIIIe-XXe siècles (Paris : Éd. du Seuil, 1999).